Performance of partitioning functional beta‐diversity indices: Influence of functional representation and partitioning methods. Issue 6 (28th March 2017) - Loiseau, Nicolas; Legras, Gaëlle; Gaertner, Jean‐Claude; Verley, Philippe; Chabanet, Pascale; Mérigot, Bastien
Abstract: Aim: Two frameworks (BASVIL and PODCAR), based on two different functional representations (ordination and dendrogram), have been proposed for partitioning overall functional beta diversity into two analogous components: turnover and nestedness‐resultant dissimilarity, or replacement and difference of functional richness, respectively. We compared the two frameworks by testing the influence of functional representations and partitioning methods on the measurement of overall functional beta diversity and its components. Innovation: We computed beta‐diversity indices from the two frameworks on a set of communities simulated according to five scenarios of assembly: random, richness gradient, pure nestedness, pure turnover and mixed turnover/loss scenarios. To disentangle the effects of the partitioning approach and those of the functional representation on measurement of functional beta diversity, we also computed PODCAR indices in multidimensional space. Main conclusions: BASVIL and PODCAR frameworks led to different results for overall functional beta diversity and their analogous partitioning components. Most of the difference between the two frameworks was due to the functional representation used. The goodness‐of‐fit measure (mean squared deviation, mSD) to assess the quality of functional spaces showed that the one computed on the basis of the dendrogram used in PODCAR remained lower than that of the functional ordination considered in BASVIL. In addition, only functional turnover derived from the BASVIL framework is independent of difference in functional richness. Finally, BASVIL measured functional variations derived from nested phenomena while PODCAR did not allow separation of this variation derived from richness difference. However, the sensitivity of BASVIL to functionally extreme species may make it difficult to know whether variations of the nestedness‐resultant dissimilarity components are due to a turnover with few extreme species or a loss in functional richness. Particular attention with regard to the properties of the two frameworks is required before drawing conclusions regarding processes that structure communities.